UPAYA ORANG TUA DALAM PENCEGAHAN TERHADAP PELECEHAN SEKSUAL ANAK USIA DINI DI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI KOTA PEKANBARU - Luthfiana Ekatami; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Sexual harassment can happen anywhere with victims regardless of age, including children. Who would have thought that many children who were still at an early age had become victims of this crime. If sexual abuse continues without any resistance, the worst thing that can happen is child rape. This kind of crime can be avoided by various efforts that can be done by the closest people to the child, namely the parents. Prevention efforts made by parents must be based on knowledge about sex education. It is important for parents to recognize sex education before implementing prevention. Therefore, this study examines the level of knowledge of parents and the efforts made by parents in preventing sexual abuse of children. This study uses the theory of rational action by Max Weber. This research method uses descriptive quantitative method with the sampling technique using the Slovin formula while the technique for determining the sample uses quota sampling. From the results of this study it can be concluded that the level of knowledge of parents regarding sex education is still not high because the results of the analysis say that the level of knowledge is still in the medium category. Prevention efforts are divided into two stages, namely the introduction stage and the implementation stage. For the introduction stage, the intensity level is already fairly high from all respondents. For the implementation stage, it is also high because according to the results of data analysis regarding the level of intensity of its implementation, it turns out that there are still many parents from Meranti Pandak Village who give close attention and supervision to their children who are still at an early age. So for the overall results of the respondents, the level of knowledge and the level of effort made are not balanced because knowledge is still in the medium category and the implementation is in the high category including high.     Keywords: Sexual Harassment, Prevention, Parents, Early Childho